Factors influencing the catalytic activity of Fe-ZSM-5 during the catalytic conversion of N₂O - Van der Walt, Franschua Johan (Centre for Catalysis Research, 2017)
Zeolites have found widespread applications as acid catalysts for decades. By introducing transition metal ions in the cation position, the zeolite is transformed into a redox catalyst. The nature of the trivalent heteroatom influences the properties of the zeolite. Contrary to Al-zeolites, Fe-containing zeolites show redox properties, since Fe can easily change its oxidation state (Fe²⁺, Fe³⁺, or Fe⁴⁺). Catalytic function of isolated redox sites within zeolite cavities (or channels) may result in a material with specific redox properties (Kiwi-Minsker et al., 2003). The properties of transition metal exchanged zeolites have been studied from the 1960's onwards and the conversion of N₂O over Fe-Y zeolites has been studied by Fu et al. (1981) in late 1970's. In this study, the preparation of iron ZSM-5 zeolite catalysts by mechanochemical means and thermally induced solid-state ion exchange was studied. After grinding the NH4-Zeolite and ferrous chloride, no x-ray reflections characteristic of ferrous chloride are detected. After heating the sample to 120 and 200 °C reflections characteristic of ferrous chloride are visible but disappear upon further heating to 300 °C. No porosity is observed after grinding and heating up to 200 °C as a result of pore mouth blocking. Moreover, upon heating up to 500 °C porosity starts to develop with pore volumes and pore sizes slightly lower than those of the parent zeolite. From the thermogravimetric analysis it is evident that the ion exchange takes place during calcination from 150 and 420 °C in agreement with the literature. In the second part of the study commercial Fe-ZSM-5 catalyst samples with different N₂O conversion activities (in the presence of H₂O and NO at 425 °C), ranging between 70 and 90 % (high, mid and low activity) are studied and characterised. The effect of temperature during calcination of the plant produced and laboratory calcined extrudate catalyst material was investigated. Panov et al. (1996) reported in the literature that the Fe²⁺ is oxidised to Fe³⁺ in the presence of N₂O forming what they called the α-oxygen, a form of active surface oxygen, with the evolution of molecular nitrogen. During the conversion, two surface α-oxygen atoms migrate, combine and desorbs as molecular oxygen from the surface. The α-oxygen forms between 200 and 350 °C and desorbs as molecular oxygen above 350 °C (Taboada et al., 2005). In this study, no correlation to N₂O conversion activity could be found for the α-oxygen content and correspondingly the concentrations of the respective iron oxides and iron hydroxides in the Fe-ZSM-5 samples.